A Possible Role for Platelet-Activating Factor Receptor in Amyotrophic Lateral Sclerosis Treatment - Briones, Marcelo R. S.; Snyder, Amanda M.; Ferreira, Renata C.; Neely, Elizabeth B.; Connor, James R.; Broach, James R. (Frontiers in Neurology, 2018)
Amyotrophic Lateral Sclerosis (ALS) is the third most prevalent neurodegenerative disease affecting upper and lower neurons. An important pathway that may lead to motor neuron degeneration is neuroinflammation. Cerebrospinal Fluids of ALS patients have increased levels of the inflammatory cytokine IL-18. Because IL-18 is produced by dendritic cells stimulated by the Platelet-activating factor (PAF), a major neuroinflammatory mediator, it is expected that PAF is involved in ALS. Here we show pilot experimental data on amplification of PAF receptor (PAFR) mRNA by RT-PCR. PAFR is overexpressed, as compared to age matched controls, in the spinal cords of transgenic ALS SOD1-G93A mice, suggesting PAF mediation. Although anti- inflammatory drugs have been tested for ALS before, no clinical trial has been conducted using PAFR specific inhibitors. Therefore, we hypothesize that administration of PAFR inhibitors, such as Ginkgolide B, PCA 4248 and WEB 2086, have potential to function as a novel therapy for ALS, particularly in SOD1 familial ALS forms. Because currently there are only two approved drugs with modest effectiveness for ALS therapy, a search for novel drugs and targets is essential.